Inactive enzymatic mutant proteins (phosphoglycerate mutase and enolase) as sugar binders for ribulose-1,5-bisphosphate regeneration reactors - De, Dinesh; Dutta, D.; Kundu, M.; Mahato, S.; Schiavone, M. T.; Chaudhuri, S.; Giri, Ashok P.; Gupta, Vidya; Bhattacharya, S. K. (Microbial Cell Factories, 2005)
Background: Carbon dioxide fixation bioprocess in reactors necessitates recycling of D- ribulose1,5-bisphosphate (RuBP) for continuous operation. A radically new close loop of RuBP regenerating reactor design has been proposed that will harbor enzyme-complexes instead of purified enzymes. These reactors will need binders enabling selective capture and release of sugar and intermediate metabolites enabling specific conversions during regeneration. In the current manuscript we describe properties of proteins that will act as potential binders in RuBP regeneration reactors. Results: We demonstrate specific binding of 3-phosphoglycerate (3PGA) and 3-phosphoglyceraldehyde ( 3PGAL) from sugar mixtures by inactive mutant of yeast enzymes phosphoglycerate mutase and enolase. The reversibility in binding with respect to pH and EDTA has also been shown. No chemical conversion of incubated sugars or sugar intermediate metabolites were found by the inactive enzymatic proteins. The dissociation constants for sugar metabolites are in the micromolar range, both proteins showed lower dissociation constant (Kd) for 3-phosphoglycerate ( 655 - 796 mu M) compared to 3-phosphoglyceraldehyde ( 822 - 966 mu M) indicating higher affinity for 3PGA. The proteins did not show binding to glucose, sucrose or fructose within the sensitivity limits of detection. Phosphoglycerate mutase showed slightly lower stability on repeated use than enolase mutants. Conclusions: The sugar and their intermediate metabolite binders may have a useful role in RuBP regeneration reactors. The reversibility of binding with respect to changes in physicochemical factors and stability when subjected to repeated changes in these conditions are expected to make the mutant proteins candidates for in-situ removal of sugar intermediate metabolites for forward driving of specific reactions in enzyme-complex reactors.

Identification of Indian pathogenic races of fusarium oxysporum f. sp ciceris with gene specific, ITS and random markers - Gurjar, Gayatri; Barve, Maneesha; Giri, Ashok P.; Gupta, Vidya (Mycologia, 2009)
In this study we demonstrate the synergistic use of gene-specific markers, ITS-RFLP, ISSR and AFLP for distinguishing Indian F. oxysporum f. sp. ciceris races. We also report for the first time that F. oxysporum f. sp. ciceris race 3, a wilt pathogen of chickpea in India, is actually E proliferatum based on phylogenetic analysis with EF-1 alpha sequence data. E oxysporum f. sp. ciceris races 1, 2 and 4 were easily distinguished from ``race 3'' (F. proliferatum) by PCR amplification with oligonucleotides designed from conserved regions of Hop78 transposon (Hop 78), cutinase (Cut), desaturase (Dst). F oxysporum f. sp. ciceris race 4 was distinguished with the xylanase 3 (xyl3) gene by absence of amplification product only in this race. The Xyl3 amplified-DNA fragment isolated and sequenced from E oxysporum f. sp. ciceris race I was similar to the F-xylanase (Xyl3) gene of E oxysporum f. sp. lycopersici. A TELD motif, which is characteristic of the F-xylanases family, was detected within the deduced amino acid sequence of F. oxysporum f. sp. ciceris. Similarly the F oxysporum f. sp. ciceris Hop78 DNA fragment, which identified ``race 3'' (E proliferatum), was homologous to the Hop78 transposon of E oxysporum f. sp. melonis, including the 100 amino acid conserved domain and the characteristic CCHC motif. The internal transcribed spacer region-restriction fragment length polymorphism (ITS-RFLP) approach along with intersimple sequence repeat (ISSR) method also differentiated ``race 3'' (F. proliferatum). Races 1 and 2 were identified by unique AFLP patterns. Sequence characterization of race-specific AFLP products revealed significant homologies of these sequences with metabolically important genes.
Keywords: AFLP; F. oxysporum f. sp ciceris races; gene specific amplification; ISSR; ITS-RFLP; race delineation; sequence characterization; translation elongation factor (EF-1 alpha)

Kernel morphometric traits in hexaploid wheat (Triticum aestivum L.) are modulated by intricate QTL x QTL and genotype x environment interactions - Prashant, Ramya; Kadoo, Narendra Y.; Desale, Charushila; Kore, Prajakta; Dhaliwal, Harcharan Singh; Chhuneja, Parveen; Gupta, Vidya (Journal of Cereal Science, 2012)
Wheat kernel size and shape influence its flour yield and market price. A hexaploid wheat population of 185 recombinant inbred lines was evaluated for five kernel morphometric traits namely, 1000-kernel weight, kernel length, width, length width ratio and factor form density in two diverse agro-climatic regions in India in five to eight year location combinations. Additive main effects and multiplicative interaction analysis revealed significant contributions from genotype (G) and genotype x environment (G x E) effects for these traits. Quantitative trait locus (QTL) analysis by composite interval mapping (CIM) was performed using a linkage map of 251 SSR markers and 59 QTLs distributed on 16 chromosomes were identified. The majority of the QTLs were located on the D genome (44.07%) and the homeologous chromosomes of Group 2 (38.98%). Stable QTLs detected in three or more year location combinations were identified for four traits. Multi-trait CIM showed 10 chromosomal regions harboring putative pleiotropic loci. Complexity in the genetic effects was further revealed by QTL analysis based on mixed-linear model that indicated 19 QTLs with significant individual effects (main-effect QTLs) and 14 QTL x QTL interactions. Five of these - nineteen main-effect QTLs and one of the fourteen QTL x QTL interactions showed environmental influence. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Epistatic QTLs; Genotype x environment interactions; Kernel size and shape; Stable QTLs

Microsatellite mapping identifies TTKST-effective stem rust resistance gene in wheat cultivars VL404 and Janz - Bansal, Urmil K.; Rebecca S. Zwart; Bhavani, Sridhar; Wanyera, Ruth; Gupta, Vidya; Bariana, Harbans S. (Molecular Breeding, 2012)
Wheat cultivar VL404 carries seedling resistance to Puccinia graminis f. sp. tritici pathotype TTKST. Monogenic segregation for seedling resistance was observed in a VL404/WL711 recombinant inbred line population and the resistance locus was temporarily designated SrVL. Bulked segregant analysis using Diversity Arrays Technology markers located SrVL on chromosome 2BL. Detailed simple sequence repeat mapping placed SrVL between gwm120 and wmc175, both at genetic distances of 3.3 cM. Based on adult plant responses of Janz and VL404 in India and Kenya, we expected these cultivars to carry the same gene against TTKST. A subset of Diamondbird/Janz doubled haploid (DH) population showed monogenic segregation, when tested against TTKST and the locus was temporarily named SrJNZ. SrVL-linked markers gwm120 and wmc175 flanked SrJNZ at a similar genetic distance, thereby confirming our hypothesis. Chromosome 2BL carries Sr9, Sr16 and Sr28. Sr9 is a multi-allelic locus and all known alleles of Sr9 and Sr16 are ineffective against TTKSK and its derivatives. A recombination value of 16.7 cM between Sr9g-linked stripe rust resistance gene Yr7 and SrJNZ in Diamondbird/Janz DH population suggested that SrJNZ is not an allele at the Sr9 locus. Based on comparison of published genetic distances between Lr13, Sr9, Sr28 and Sr16 with that observed in this study, we concluded SrVL and SrJNZ to be Sr28. This gene was contributed by a common parent Gabo, which also exhibited resistance against TTKST. Sr28-linked markers gwm120 and wmc175 confirmed the presence of this gene in a high proportion of Australian cultivars that showed stem rust resistance in Kenya. These markers can be used for marker-assisted pyramiding of Sr28 with other stem rust resistance genes.
Keywords: Disease resistance; Markers; Stem rust; Ug99; Wheat

Characterization of three novel isoprenyl diphosphate synthases from the terpenoid rich mango fruit - Kulkarni, Ram; Pandit, Sagar; Chidley, Hemangi G.; Nagel, Raimund; Schmidt, Axel; Gershenzon, Jonathan; Pujari, Keshav; Giri, Ashok P.; Gupta, Vidya (Plant Physiology and Biochemistry, 2013)
Mango (cv. Alphonso) is popular due to its highly attractive, terpenoid-rich flavor. Although Alphonso is clonally propagated, its fruit-flavor composition varies when plants are grown in different geo-climatic zones. Isoprenyl diphosphate synthases catalyze important branch-point reactions in terpenoid biosynthesis, providing precursors for common terpenoids such as volatile terpenes, sterols and carotenoids. Two geranyl diphosphate synthases and a farnesyl diphosphate synthase were isolated from Alphonso fruits, cloned for recombinant expression and found to produce the respective products. Although, one of the geranyl diphosphate synthases showed high sequence similarity to the geranylgeranyl diphosphate synthases, it did not exhibit geranylgeranyl diphosphate synthesizing activity. When modeled, this geranyl diphosphate synthase and farnesyl diphosphate synthase structures were found to be homologous with the reference structures, having all the catalytic side chains appropriately oriented. The optimum temperature for both the geranyl diphosphate synthases was 40 degrees C and that for farnesyl diphosphate synthase was 25 degrees C. This finding correlated well with the dominance of monoterpenes in comparison to sesquiterpenes in the fruits of Alphonso mango in which the mesocarp temperature is higher during ripening than development. The absence of activity of these enzymes with the divalent metal ion other than Mg2+ indicated their adaptation to the Mg2+ rich mesocarp. The typical expression pattern of these genes through the ripening stages of fruits from different cultivation localities depicting the highest transcript levels of these genes in the stage preceding the maximum terpene accumulation indicated the involvement of these genes in the biosynthesis of volatile terpenes. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Alphonso; Flavor variation; Fruit; Isoprenyl diphosphate synthase; Mangifera indica; Terpene volatiles

Oxidoreductase from `Alphonso' mango catalyzing biosynthesis of furaneol and reduction of reactive carbonyls - Kulkarni, Ram; Chidley, Hemangi G.; Deshpande, Ashish; Schmidt, Axel; Pujari, Keshav; Giri, Ashok P.; Gershenzon, Jonathan; Gupta, Vidya (SpringerPlus, 2013)
Two furanones, furaneol (4-hydroxy-2,5-dimethyl-3(2H)-furanone) and mesifuran (2,5-dimethyl-4-methoxy-3(2H)-furanone), are important constituents of flavor of the Alphonso cultivar of mango (Mangifera indica). To get insights into the biosynthesis of these furanones, we isolated an enone oxidoreductase gene from the Alphonso mango. It has high sequence similarity to an alkenal/one oxidoreductase from cucumber (79% identity) and enone oxidoreductases from tomato (73% identity) and strawberry (72% identity). The complete open reading frame was expressed in E. coli and the (his) 6-tagged recombinant protein was purified by affinity chromatography. The purified protein assayed with NADH as a reducing agent converted D-fructose-1,6-diphosphate into furaneol, the immediate precursor of mesifuran. The enzyme was also able to convert two highly reactive carbonyls, 3-buten-2-one and 1-penten-3-one, produced by lipid peroxidation in plants, into their saturated derivatives. Expression profiling in various ripening stages of Alphonso fruits depicted an expression maxima at 10 days after harvest stage, shortly before the appearance of the maximum amount of furanones (completely ripe stage, 15 days after harvest). Although no furanones were detected at the 0 day after harvest stage, significant expression of this gene was detected in the fruits at this stage. Overall, the results suggest that this oxidoreductase plays important roles in Alphonso mango fruits.
Keywords: Detoxification; Enone oxidoreductase; Flavor; Mangifera indica; Ripening

Biocatalyst development for lactic acid production at acidic pH using inter-generic protoplast fusion - Singhvi, Mamata; Gurjar, Gayatri; Gupta, Vidya; Gokhale, Digambar V. (RSC Advances, 2015)
Global warming and environmental problems force us to develop sustainable processes based on the use of biocatalysts that are eco-friendly with the least potential toxicity. Lactic acid fermentation at neutral pH generates a large amount of gypsum during down-stream processing. Hence it is essential to develop Lactobacillus strains which produce lactic acid at acidic pH thus making the whole downstream process environmentally friendly. Fusant F3 was generated using protoplast fusion between Lactobacillus delbrueckii Mut Uc-3 and Acetobacter pasteurianus NCIM 2314 on solid media at pH 4.0. Fusant F3 was further treated by UV irradiation to generate a mutant, FM1, with improvements in acid tolerance which produced five-fold more lactic acid than the parent strain at acidic pH. The molecular studies using RAPD markers demonstrated that the fusant is derived from both the parental strains, Acetobacter and Lactobacillus and the mutant is derived from the fusant. The utilization of such acid tolerant strains could be able to produce free lactic acid at acidic pH without using neutralizing agents and will offer an effective means for designing environmentally benign processes for lactic acid production.

Genotype x environment interactions and QTL clusters underlying dough rheology traits in triticum aestivum L. - Prashant, Ramya; Mani, Elangovan; Rai, Richa; Gupta, R. K.; Tiwari, Ratan; Dholakia, Bhushan B.; Oak, Manoj; Roeder, Marion; Kadoo, Narendra Y.; Gupta, Vidya (Journal of Cereal Science, 2015)
Genetic dissection of dough rheology traits (DRT) in hexaploid wheat was carried out using nine mixograph characters evaluated in two consecutive years in three agro-climatic zones in India in an RIL population (HI977 x HD2329). Pearson correlations determined in each year-location indicated 15 stable trait inter-relationships among them but inconsistent correlations with loaf volume (LV) were observed. Using AMMI analysis we derived patterns in G x E interactions (GEI) indicating 6-47% contribution for the DRT. Composite interval mapping using a linkage map of 202 SSR markers identified 144 DRT QTLs of which, 96 were detected in single- and the rest in two to five year-locations. Sixteen QTL clusters located on ten chromosomes were identified and only three of them on chromosomes 1B, 5B and 6D involved LV QTLs. For each trait, majority of the DRT QTLs detected in single as well as multiple environments showed location-specificity and suggested that owing to GEI, breeding for wheat dough quality might need careful selection of QTLs targeted for individual agro-climatic zones. The inconsistent correlations of DRT and LV and differential locations of their QTLs in this population corroborated that using dough rheological traits alone to predict LV might pose challenges during wheat improvement. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: AMMI analysis; Dough rheology; Mixograph; QTL

Biosynthesis of anti-proliferative gold using endophytic fusarium oxysporum strain isolated from neem (A-indica) leaves - Siddiqui, Ejaz Ahmad; Ahmad, Absar; Julius, Anju; Syed, Asad; Khan, Shadab; Kharat, Mahesh; Pai, Kalpana; Kadoo, Narendra Y.; Gupta, Vidya (Current topics in medicinal chemistry, 2016)
Here we report a simple, rapid, environment friendly approach for the synthesis of gold nanoparticles using neem (Azadirachta indica A. Juss.) fungal endophyte, which based upon morphological and cultural characteristics was eventually identified as Fusarium oxysporum. The aqueous precursor (HAuCl4) solution when reacted with endophytic fungus resulted in the biosynthesis of abundant amounts of well dispersed gold nanoparticles of 10-40 nm with an average size of 22nm. These biosynthesized gold nanoparticles were then characterized by standard analytical techniques such as UV-Visible spectroscopy, X-ray diffraction, Transmission Electron Microscopy and Fourier Transform Infrared Spectroscopy. Cytotoxic activity of these nanoparticles was checked against three different cell types including breast cancer (ZR-75-1), Daudi (Human Burkitt's lymphoma cancer) and normal human peripheral blood mononuclear cells (PBMC), where it was found that our gold nanoparticles are anti-proliferative against cancer cells but completely safe toward normal cells. In addition to this, assessment of toxicity toward human RBC revealed less than 0.1 % hemolysis as compared to Triton X-100 suggesting safe nature of our biosynthesized gold nanoparticles on human cells. Also, our nanoparticles exhibited no anti-fungal (against Aspergillus niger) or anti-bacterial [against Gram positive (Bacillus subtilis & Staphylococcus aureus) and Gram negative (Escherichia coli & Pseudomonas aeruginosa) bacteria] activity thus suggesting their non-toxic, biocompatible nature. The present investigation opens up avenues for eco-friendly, biocompatible nanomaterials to be used in a wide variety of application such as drug delivery, therapeutics, theranostics and so on.

Identification and functionality prediction of pathogenesis-related protein 1 from legume family - Tellis, Meenakshi; Mathur, Monika; Gurjar, Gayatri; Kadoo, Narendra; Gupta, Vidya (Proteins-Structure Function and Bioinformatics, 2017)
The production and accumulation of pathogenesis-related (PR) proteins in plants is one of the important responses to biotic and abiotic stress. Large number of identified PR proteins has been categorized into 17 functional families based on their structure, phylogenetics, and biological activities. However, they are not widely studied in legume crops. Using 29 PR1 proteins from Arabidopsis thaliana, as query, here we have predicted 92 candidate PR1 proteins through the PSI-BLAST and HMMER programs. These candidate proteins were comprehensively analyzed with, multiple sequence alignment, domain architecture studies, signal peptide, and motif extraction followed by phylogenetic analysis. Further, response of two candidate PR1 proteins from chickpea against Fusarium oxysporum f.sp.ciceri attack was validated using qRT-PCR followed by their 3D structure prediction. To decipher mode of action for PR1s, docking of pathogen extracellular matrix components along with fungal elicitors was performed with two chickpea PR1 proteins. Based on these findings, we propose carbohydrate to be the unique pathogen-recognition feature for PR1 proteins and beta-glucanase activity via beta-glucan binding or modification.

Pharmaceutical standardization and physicochemical characterization of traditional ayurvedic marine drug: incinerated conch shell (shankha bhasma) - Chavan, Sandeep; Tayade, Sonali; Gupta, Vidya; Deshmukh, Vineeta; Sardeshmukh, Sadanand (Marine Drugs, 2018)
Natural resources such as plants, animals and minerals have always been used by mankind to develop drugs and marine world is no exception. Marine by-products like conches, pearls, mother of pearl shells, corals and so forth have been used by traditional Ayurvedic practitioners for centuries. The unique methods of these preparations are scientifically designed to eliminate unwanted impurities and convert them into bioavailable form. In this study, Conch (Xanchus pyrum) was used as a marine resource of calcium carbonate and was converted pharmaceutically from its aragonite form to calcite. All the steps of preparations and changes in the properties therein were documented and validated. Further, traditional as well as modern analytical tools were used to study its physical and chemical characters to develop a monograph. The physical characterization included particle size, X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA) and Fourier Transform Infra-red (FTIR). Metal composition and heavy metal limits were determined using Inductively Coupled Plasma Optical Emission Spectrometry (ICPOES). This study revealed the rearrangement of aragonite crystals into calcite form by grinding, trituration with aloe vera juice and incineration under controlled conditions. Moreover, the finished product was found to be devoid of organic matrix that is nacre. This study creates a foundation for the development of a master formula for commonly used Shankha Bhasma in Ayurvedic medicines.

Biodegradation of squalene and n-hexadecane by Gordonia amicalis HS-11 with concomitant formation of biosurfactant and carotenoids - Sowani, Harshada; Deshpande, Ashish; Gupta, Vidya; Kulkarni, Mohan; Zinjarde, Smita (International Biodeterioration & Biodegradation, 2019)
Gordonia amicalis HS-11 has been enriched from a hydrocarbon contaminated tropical soil sample. The ability of this organism to utilize a triterpenic polyunsaturated hydrocarbon, squalene (2,6,10,15,19,23-hexamethyl-6,6,10,14,18,20-tetracosahexane) and the model saturated hydrocarbon n-hexadecane is described here. The isolate degraded squalene and n-hexadecane (79 +/- 3.02 and 96 +/- 4.11%, respectively) after eight days of incubation. The isolate produced an extracellular biosurfactant that reduced surface tension from 69 +/- 2.83 to 40 +/- 1.63 and 35 +/- 2.34 mN m(-1) with squalene and n-hexadecane as carbon sources, respectively, after 6 days. The Actinomycete cleaved squalene to geranylacetone and famesyl acetaldehyde that were further utilized for supporting growth. n-Hexadecane was degraded via monoterminal oxidation and activities of important enzymes (alkane hydroxylase and alcohol dehydrogenase) were highest (215 +/- 8.76 and 169 +/- 6.02 units mg(-1) protein, respectively) after four days. Cells grown on squalene were short and with n-hexadecane there were clumps of longer cells. Squalene and n-hexadecane-grown cell surfaces were smooth possibly due to extracellular surface active compounds. While growing on hydrophobic substrates, some cells were seen adhering to droplets and others were in the free form. The culture was able to simultaneously degrade hydrocarbons and produce two commercially relevant value-added products. The yield of the extracellular biosurfactant on n-hexadecane was 480 mg l(-1) and cells grown on squalene and n-hexadecane also yielded carotenoids (2.3 +/- 0.14 and 2.9 +/- 0.10 mg g(-1) dry cell weight, respectively). This is the first report on the utilization of squalene by Gordonia.
Keywords: Aerobic biodegradation; Carotenoids; Catabolic pathways; Emulsifier; Gordonia amicalis HS-11

Effect of media components and growth conditions for improved linoleic acid production by beauveria species - Sanghi, Smrati; Chirmade, Tejas; More, Snehal; Prabhune, Asmita; Gupta, Vidya; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2019)
Beauveria species are well-known insect pathogenic fungi, and Beauveria bassiana is used as a biopesticide against various pests in agriculture. However, the Beauveria species has not been reported as producers of microbial oils. In this study, Beauveria spp. MTCC 5184 was used to produce microbial oil with high linoleic acid (LA) content. Ten experiments were performed to evaluate the effects of several media parameters, such as carbon and nitrogen sources, pH, various concentrations of carbon and nitrogen, growth duration, and oleic acid (OLA) supplementation for maximum LA and dry biomass production by the fungus. Several of these parameters had a significant impact on the production of LA, as well as dry biomass. The glucose yeast extract (GYE) medium supplemented with 1.5% (w/v) peptone yielded maximum LA (0.32 +/- 0.01 g L-1) and biomass (5.51 +/- 0.26 g L-1). However, through the addition of 1.0% (w/v) OLA, the precursor of LA, LA production was enhanced 12-fold (1.24 +/- 0.03 g L-1), and the biomass production increased by 5-fold (11.05 +/- 0.46 g L-1) in comparison to those in the basal (GYE) medium. Using lactose as the sole carbon source produced the lowest LA (0.05 +/- 0.00 g L-1) and biomass (1.04 +/- 0.10 g L-1). The results of this study will be useful for the commercial exploitation of this fungus for the production of LA-rich microbial oil for use in the production of lubricants, greases, paints, cosmetics, etc.

Metabolomic dynamics reveals oxidative stress in spongy tissue disorder during ripening of mangifera indica l. fruit - Oak, Pranjali; Deshpande, Ashish; Giri, Ashok; Gupta, Vidya (Metabolites, 2019)
Spongy tissue disorder, a mesocarp specific malady, severely affects the flavor and pulp characters of Alphonso mango fruit reducing its consumer acceptability. Here, we investigated comparative metabolomic changes that occur during ripening in healthy and spongy tissue-affected fruits using high resolution mass spectrometric analysis. During the spongy tissue formation, 46 metabolites were identified to be differentially accumulated. These putative metabolites belong to various primary and secondary metabolic pathways potentially involved in maintaining the quality of the fruit. Analysis revealed metabolic variations in tricarboxylic acid cycle and gamma amino butyric acid shunt generating reactive oxygen species, which causes stressed conditions inside the mesocarp. Further, reduced levels of antioxidants and enzymes dissipating reactive oxygen species in mesocarp deteriorate the fruit physiology. This oxidative stress all along affects the level of amino acids, sugars and enzymes responsible for flavor generation in the fruit. Our results provide metabolic insights into spongy tissue development in ripening Alphonso mango fruit.
Keywords: gamma amino butyric acid shunt; mango metabolomics; Oxidative stress; spongy tissue disorder; tricarboxylic acid cycle

Comparative proteomics unravels the differences in salt stress response of own-rooted and 110R-grafted thompson seedless grapevines - Patil, Sucheta; Shinde, Manisha; Prashant, Ramya; Kadoo, Narendra; Upadhyay, Anuradha; Gupta, Vidya (Journal of Proteome Research, 2020)
Thompson Seedless, a commonly grown table grape variety, is sensitive to salinity when grown on its own roots, and therefore, it is frequently grafted onto salinity-tolerant wild grapevine rootstocks. Rising soil salinity is a growing concern in irrigated agricultural systems. The accumulation of salts near the root zone severely hampers plant growth, leading to a decrease in the productive lifespan of grapevine and causing heavy yield losses to the farmer. In the present study, we investigated the differences in response to salinity between own-rooted Thompson Seedless (TSOR) and 110R-grafted Thompson Seedless (TS110R) grapevines, wherein 110R is reported to be a salt-tolerant rootstock. The grapevines were subjected to salt stress by treating them with a 150 mM NaCl solution. The stress-induced changes in protein abundance were investigated using a label-free shotgun proteomics approach at three time points viz. 6 h, 48 h, and 7 days of salt treatment. A total of 2793 proteins were identified, of which 246 were differentially abundant at various time-points in TSOR and TS110R vines. The abundance of proteins involved in several biological processes such as photosynthesis, amino acid metabolism, translation, chlorophyll biosynthesis, and generation of precursor metabolites was significantly affected by salt stress in both the vines but at different stages of stress. The results revealed that TSOR vines responded fervently to salt stress, while TS110R vines adopted a preventive approach. The findings of this study add to the knowledge of salinity response in woody and grafted plants and hence open the scope for further studies on salt stress-specific differences induced by grafting.
Keywords: 110R rootstock; gene ontology; grafting; label-free proteomics; salt stress; Vitis vinifera

Simultaneous identification and estimation of glycyrrhizin, glabridin, and 18β‐glycyrrhetinic acid in de‐glycyrrhized Ayurvedic lipid‐based formulation of Glycyrrhiza glabra using dual wavelength reverse phase‐high‐performance liquid chromatography - Kumbhalkar, Bhagyashri; Walunj, Tanhaji; Chavan, Sandeep; Gupta, Vidya; Deshmukh, Vineeta; Sardeshmukh, Sadanand (Separation Science Plus, 2020)
Plant‐based Ayurvedic formulations such as medicated oils, confectioneries, etc. are developed with a rationale of selecting specific compounds for targeted action and minimal side effects. It is imperative to develop an analytical method to simultaneously identify and quantify the targeted compounds for good resolution with low retention time. The present assay using reverse phase‐high‐performance liquid chromatography is optimized to resolve glycyrrhizin, glabridin, and 18β‐glycyrrhetinic acid simultaneously at retention times of 6.6, 8.1, and 10.2 min, respectively, using acidified mobile phase from Glycyrrhiza glabra utilized in Ayurvedic lipid (cow's ghee and sesame oil) based formulations. Raw material, its decoction, and residues formed during preparation steps were extracted in methanol while lipid formulations were extracted using a binary solvent system of methanol and n‐hexane. The separation was performed on Hypersil gold column maintained at 40°C using 0.2% ortho‐phosphoric acid with pH 3.5 in water and acetonitrile as binary gradient mobile phase. The compounds were detected at wavelengths 230 (glabridin) and 254 (glycyrrhizin and 18β‐glycyrrhetinic acid) nm. The method revealed de‐glycyrrhized finished products containing glabridin and 18β‐glycyrrhetinic acid having medicinal value.

Antimicrobial and antioxidant potential of a standardized ayurvedic formulation explains its clinical efficacy as gargles in post-radiotherapy oral cancer patients - Chavan, Sandeep; Bhuvad, Sushama; Kumbhlakar, Bhagyashri; Auti, Jyoti; Walunj, Tanhaji; Pathak, Shridevi; Tanpure, Rahul; Gujar, Shweta; Shinde, Jagdish; Kulkarni, Arvind; Gupta, Vidya; Deshmukh, Vineeta; et al. (Journal of Herbal Medicine, 2021)
Introduction: Exploring the antioxidant and antimicrobial potential of a standardized proprietary poly-herbal powder and evaluating its clinical efficacy as an Ayurvedic gargle (Gandush) for reducing oral microbial load and side effects of radiotherapy in oral cavity cancer patients was the aim of this pilot study. Methods: Formulation (Gandush Churna) comprising Terminalia chebula Retz., Terminalia bellirica (Gaertn.) Roxb., Phyllanthus emblica L. and Curcuma longa L. and its decoction (Gandush Kwath) were standardized. In-vitro antioxidant potential and antimicrobial activity against selective bacterial and fungal strains were studied. Oral cavity cancer patients who had undergone radiotherapy were enrolled. The decoction was prepared by soaking Gandush Churna in water, boiling and reducing by 50 %; and was used for gargling, twice a day, for 7 days. Total microbial count and identification of microbiota in the oral cavity as well as symptoms graded as per Common Terminology Criteria for Adverse Events, were noted before and after the treatment. Change in microbial load and shift in symptom gradations were analyzed. Results: A monograph with physicochemical, chromatography, safety and stability parameters was developed. The decoction possessed good in-vitro antioxidant and antimicrobial activities. Gargling therapy significantly reduced bacterial load while mildly controlled the fungal infection in oral cavity cancer patients. It significantly reduced the severity of symptoms viz. stomatitis and local pain, with considerably decreased xerostomia and dysphagia. Conclusions: Intervention of gargle therapy using poly-herbal formulation may serve as an effective complementary treatment to improve oral hygiene and reduce side effects of radiotherapy in oral cancer patients.
Keywords: Anti-microbial; Antioxidant; Gandush; Gargle therapy; Oral cavity cancers; Radiotherapy side effects

Genome wide analysis of 14-3-3 proteins in Cicer arietinum L. and identification of isoforms responsive to Fusarium oxysporum - Gurjar, Gayatri; Nimbalkar, Suhas; Giri, Ashok; Gupta, Vidya (Current Science, 2021)
In the present study, we have identified and characterized two 14-3-3 isoforms, namely isoform A and C from chickpea (Cicer arietinum L.), that might play a crucial role during disease resistance. Further, in silico analysis of these 14-3-3 proteins was accomplished, including motif identification and structure prediction from deduced amino acid sequences. Expression profiling of the two representative 14-3-3 isoforms in the roots of wilt resistant and susceptible chickpea varieties upon Fusarium oxysporum f. sp ciceri race 1 (FOC1) challenge, revealed time dependent isoform specific differential expression in induced chickpea roots upon FOC1 colonization.
Keywords: Bioinformatics; chickpea 14-3-3s; pathogen responsive; transcriptional analysis

Transcriptional and translational perturbation in abiotic stress induced physiological activities and metabolic pathway networks in spongy tissue disorder of mango fruit - Oak, Pranjali; Jha, Vineet; Deshpande, Ashish; Tanpure, Rahul; Dawkar, Vishal; Mundhe, Swapnil; Ghuge, Sandeep; Prabhudesai, Shrikant; Krishanpal, Anamika; Jere, Abhay; Giri, Ashok; Gupta, Vidya (Postharvest Biology and Technology, 2022)
Spongy tissue formation is economically the most detrimental but agriculturally less focused physiological disorder in mango. `Alphonso' cultivar is highly prone to oxidative stress induced spongy tissue disorder impacting biochemical and metabolic profile, thereby affecting pulp quality and nutritional value of the fruit. In the present study, comparative analysis of spongy and healthy mesocarp tissues of `Alphonso' mango by transcriptomics using Illumina sequencing and proteomics using LC-MS approaches, respectively identified and quantified many genes and proteins in the metabolic pathways responsible for the spongy tissue development. The table green and the mid ripe stages of `Alphonso' fruit ripening were evaluated by the transcriptomic study and outcomes were validated using proteomic investigations for all the four ripening stages. Colossal amount of data including 30,582 transcripts, 10,800 gene ontologies and 387 putative proteins was generated from this analysis. Current multi-omics exploration revealed the development of abiotic stress (mainly oxidative stress) induced perturbations in various metabolic pathways and their interconnections, leading to the spongy tissue formation in mango. This further unfolded the altered cell wall degradation, ethylene and flavonoid biosynthesis, fruit ripening and flavor formation, thus hampering the fruit specific characteristics in mango with spongy tissue disorder.
Keywords: Oxidative stress; Proteome; spongy tissue disorder; Transcriptome; ` Alphonso ` mango

Structure of epoxide hydrolase 2 from Mangifera indica throws light on the substrate specificity determinants of plant epoxide hydrolases - Bhoite, Ashwini; Gaur, Neeraj K.; Palange, Megha; Kontham, Ravindar; Gupta, Vidya; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2024)
Epoxide hydrolases (EHs) are a group of ubiquitous enzymes that catalyze hydrolysis of chemically reactive epoxides to yield corresponding dihydrodiols. Despite extensive studies on EHs from different clades, generic rules governing their substrate specificity determinants have remained elusive. Here, we present structural, biochemical and molecular dynamics simulation studies on MiEH2, a plant epoxide hydrolase from Mangifera indica. Comparative structure-function analysis of nine homologs of MiEH2, which include a few AlphaFold structural models, show that the two conserved tyrosines (MiEH2Y152 and MiEH2Y232) from the lid domain dissect substrate binding tunnel into two halves, forming substrate-binding-pocket one (BP1) and two (BP2). This compartmentalization offers diverse binding modes to their substrates, as exemplified by the binding of smaller aromatic substrates, such as styrene oxide (SO). Docking and molecular dynamics simulations reveal that the linear epoxy fatty acid substrates predominantly occupy BP1, while the aromatic substrates can bind to either BP1 or BP2. Furthermore, SO preferentially binds to BP2, by stacking against catalytically important histidine (MiEH2H297) with the conserved lid tyrosines engaging its epoxide oxygen. Residue (MiEH2L263) next to the catalytic aspartate (MiEH2D262) modulates substrate binding modes. Thus, the divergent binding modes correlate with the differential affinities of the EHs for their substrates. Furthermore, long-range dynamical coupling between the lid and core domains critically influences substrate enantioselectivity in plant EHs.
Keywords: Enantioselectivity; Epoxide hydrolase; molecular dynamics simulation; Regioselectivity; X-ray crystallography